IMPLEMENTATION OF MARKETING STRATEGY IN INCREASING CHINA MARKET TO STAY AT GRAND INNA KUTA THROUGH AFTERNOON TEA SALES - Putu Elita Rembulan; I Ketut Astawa; I Ketut Budarma (Politeknik Negeri Bali, 2020)
This study discusses the strengths and weaknesses of the strategic marketing mix owned by the Grand Inna Kuta hotel. The data collection technique used was purposive sampling. Data collection was carried out by observation, interview, documentation study, and distributing questionnaires with a total number of respondents as many as 14 respondents consisting of relevant departments of the Sales and Marketing Department and the Food & Beverage Department. The analysis technique used in this study is the SWOT analysis technique (Strength, Weakness, Opportunity, Threat). In the results of the study there were 9 internal indicators that became strengths, and 7 internal indicators that became weaknesses. Then, there are 3 external indicators that become opportunities, and 3 external indicators that pose a threat. In the SWOT matrix analysis technique, there are 2 strategies for maximizing strength and opportunity, namely providing attractive prices and adding new menu variants, 3 strategies to maximize strength to minimize obstacles that consist of replacing furniture with new ones, adding music to restaurants, and presenting products creatively, 2 strategies to maximize opportunities by minimizing weaknesses are by paying attention to where the products are presented and adding special items, and 2 strategies to minimize threats and weaknesses such as giving special prices for booking groups and redesigning layouts rather than restaurants.